Penerapan “Blind SAIH” dalam 7 Kebiasaaan Anak Indonesia Hebat untuk Meningkatkan Penguatan Karakter Murid Hambatan Penglihatan - Nickita Kiki Praditya (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Best practice to support the implementation of 7 KAIH is carried out by making modifications to the Great Indonesian Children's Gymnastics (SAIH) for students with visual impairments. Modifications to the Great Indonesian Children's Gymnastics